EFFECT OF UREA FEEDING ON FEED INTAKE AND PERFORMANCE OF MALE BUFFALO CALVES - A. R. Burque; M. Abdullah; M.E. Babar; K. Javed; H. Nawaz (Journal of Animal and Plant Sciences, 2008)
Feed intake, growth rate, feed efficiency and carcass characteristics of male buffalo calves, fed different levels of urea, were investigated. Feeding trials were conducted using 54 male buffalo calves of the Nili-Ravi breed in three experiments. Seven experimental rations were prepared by adding fertilizer grade urea at the levels of 0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 percent, replacing undecorticated cottonseed cake and wheat bran on nitrogen equivalent basis. A ration without urea served as control. At the termination of the feeding trials, 3 calves from each group were slaughtered and carcass data were obtained. It was found that intake of dry matter decreased as the level of urea increased in the ration. The depression in dry matter intake was significant when the urea level exceeded 2.0 percent. Weight gains of calves were significantly higher on urea ration up to 1.0% as compared to control. Almost similar weight gains were observed up to 2.0 percent levels of urea. However beyond this level, i.e. at 2.5 and 3.0 percent, a significant decline in weight gain was observed. The effect of urea feeding with respect to feed efficiency was nearly of the same magnitude as on weight gain. The slaughter data revealed a non-significant difference in the dressing percentage of the carcasses of calves fed 0, 0.5, 1.0, I 5 and 2.0 percent urea in their rations. However, the carcass quality was adversely affected when urea was used beyond 2.0 percent level. Gristles were significantly increased (by about 40%) in the carcasses of calves fed 3.0 percent urea compared to the control animals. Acceptability score through organoleptic tests of cooked meat showed no significant difference between control and 2.0 percent urea fed animals.
Keywords: Urea feeding; Feed intake; Performance; Buffalo calves